ANALYSIS OF BITCOIN LEGALIZATION AS AN OFFICIAL TRANSACTION TOOL IN EL SALVADOR: ANALISIS LEGALISASI BITCOIN SEBAGAI ALAT TRANSAKSI RESMI DI EL SALVADOR - Lirih Hayyu Maghfiroh; Sri Yuniati; Adhiningasih Prabhawati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
This research begins with the phenomenon of the emergence of Cryptocurrency, one of which is Bitcoin, which is used as currency in El Salvador. In this regard, the research aims to question El Salvador's reasons for legalizing Bitcoin as an official means of transaction. This paper answers questions through qualitative methods using secondary data. The data were then analyzed using a qualitative descriptive analysis. The results of this study indicate that El Salvador's reason for legalizing Bitcoin is to reduce dependence on the United States dollar, attract investors from abroad, and improve the El Salvador economy.